Note on the Decomposition of Gini Inequality - Sastry, D. V. S.; Kelkar, Ujwala R. (The Review of Economics and Statistics, 1994)
The purpose of this note is to propose a decomposition of the Gini index of inequality into within and between subpopulations using the Lerman-Yitzhaki covariance method. The present method suggests that once the population is arranged in ascending order of income and assigned ranks, the same ranks will be used to calculate total as well as between inequality. In this way, it differs from the one suggested by Jacques Silber (1989) in the measurement of between inequality and, thereby, in the interaction term. Copyright 1994 by MIT Press.